Congenital Histidine-Rich Glycoprotein Deficiency - Shigekiyo, Toshio; Ohshima, Tsutomu; Oka, Hirofumi; Tomonari, Akira; Azuma, Hiroyuki; Saito, Shiro (Thrombosis and Haemostasis, 1993)
The proband, a 43-year-old woman, suffered from right transverse sinus thrombosis during oral contraceptive treatment. A month after stopping the drug, her plasma activities of antithrombin III, protein C, protein S, heparin cofactor II, plasminogen and plasminogen activator inhibitor were normal, but her plasma histidine-rich glycoprotein (HRG) level was only 21% of the normal level of 109.5 ± 51.5% (mean ± 2 SD). The HRG concentrations in her plasma determined on four different occasions over 6 months were similar. She showed no clinical signs of liver insufficiency or sepsis. Low levels of plasma HRG (20% to 35% of normal) were also found in her aunt, uncle and two daughters. These results suggest that congenital HRG deficiency is inheritary in this family.